Evaluation acute and sub-chronic toxicity assessments of Oleo-gum Resin of Ferula assa-foetida L. in Wistar rats - Zahra Tofighi; Razieh Mohammad Jafari; Masoud Besati; Mostafa Pirali Hamedani; Abbas Hadjiakhoondi; Zahra Baharipour; Ahmad Jariani; Zahra Moiin; Saeed Tavakoli; Saied Goodarzi (Institue of Medicinal Plants, ACECR, 2023)
Background: Ferula assa-foetida is an herbaceous plant from Apiaceae family. Several pharmacological effects of oleo-gum resin of this plant were introduced in modern and traditional medicines such as digestive, antimicrobial, anti-diabetic, appetizing, insecticidal, and etc. Objectives: This study aimed to acute and sub-chronic toxicity of chloroform fraction of oleo-gum extract of Ferula in Wistar rats. The safety of this can guarantee its use in treatment and various industries. Methods: Rats in six groups including male and female (kept separately) at different doses (50 mg/kg, 500 mg/kg, and 2000 mg/kg) and two control groups (control and DMSO( were selected to evaluate the acute toxicity of chloroform fraction of Ferula. For 30 days, 50 mg/kg and 250 mg/kg of sample was administrated to male and female rats. Mortality, appearance and behavioral changes, food intake, the weight of rats, and hematological, biochemical variables and histopathological changes were examined. Results: Physical and behavioral changes were not observed in acute and sub-chronic toxicity conditions. Food intake significantly differed between male and female DMSO control and other groups. In biochemical variables study, only SGOT (AST) showed a significant difference from the control group (DMSO) in acute toxicity and BUN, ALP and SGOT (AST) in sub-chronic toxicity. Also, any histopathological change was observed in spleen, liver, and kidney organs. Conclusion: Oleo-gum resin of F. assa-foetida has not toxic effects, so it should be used with caution in the long term.